Valoración funcionall en pacientes con fractura de muñeca tratados con osteodesis. - Peralta González, Kleber Michael (2014)
The present study "Functional valuation in patients with wrist fracture treated osteodesis" was realized in the Manuel YgnacioMonteros Hospital IESS Loja, in the period from July to December 2013.The objective of the investigation is to determine the functional results of the patients with fracture metaphysis distal of radio treated with osteodesis, the age and sex in which one presents with major frequency, and the employment condition of the patients after the treatment. It is a transversal, descriptive, observational study, realized by means of the compilation of information of the patients in the System AS400 of the Manuel YgnacioMonterosHospital, through telephone calls to and direct surveys we applied the Clinical - functional scale of wrist of the May Clinic to assess the functional results obtained after treatment performed. Subsequently the corresponding statistical analysis was performed, to thereby obtain the results according to the objectives. The study was realized by a total of 48 patients, over 13 years old that presented fracture distal metaphysis of radio of type Fernandez I and II that were treated with osteodesis. Obtaining that the ages of major presentation are between 13-17 years in the masculine sex and major of 53 years in the feminine sex. Bearing in mind the labor condition one determined that a total of 28 patients corresponding to 58 % had a regular rehabilitation to his labors of work. In addition determined that the patients of 13-17 year old obtained excellent results with the treatment realized in 88,2 %, whereas the patients major 53-year-old obtained good results at 57,9 %. Upon completion of the work and then analyzing the results it is concluded that treatment with osteodesis performed in patients with fracture distal metaphysis of radio realized in Manuel YgnacioMonterosHospital is appropriate and excellent results were obtained in 56.25 % of patients. Key words: Fracture, wrist, distal metaphysis of radio, Osteodesis, Clinical - functional scale of wrist of the May Clinic.